1991
DOI: 10.1001/jama.1991.03460160057029
|View full text |Cite
|
Sign up to set email alerts
|

Concordance for Dyslipidemic Hypertension in Male Twins

Abstract: Sixty cases of dyslipidemic hypertension were identified in the 1028 middle-aged, white, male twin participants in the first examination of the National Heart, Lung, and Blood Institute Twin Study (1969 to 1973). The prevalence of dyslipidemic hypertension was similar by zygosity but proband concordance was three times greater in monozygotic than dizygotic twins (0.44 [seven concordant and 18 discordant pairs] vs 0.14 [two concordant and 24 discordant pairs]), suggesting a genetic effect on the condition. Low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 19 publications
4
30
1
Order By: Relevance
“…Others have demonstrated a higher incidence of the syndrome of insulin resistance in FCH subjects but this was found to be associated with obesity ( 15,18). In the present study, obesity was not a feature in FCH subjects since the mean body mass index in the tertiles was lower than in the study ofHunt et al ( 15) and Selby et al ( 18). Nonetheless, in the present study insulin concentrations correlated significantly with the body mass index in FCH relatives.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Others have demonstrated a higher incidence of the syndrome of insulin resistance in FCH subjects but this was found to be associated with obesity ( 15,18). In the present study, obesity was not a feature in FCH subjects since the mean body mass index in the tertiles was lower than in the study ofHunt et al ( 15) and Selby et al ( 18). Nonetheless, in the present study insulin concentrations correlated significantly with the body mass index in FCH relatives.…”
Section: Discussioncontrasting
confidence: 55%
“…Insulin resistance which has been associated to increased atherosclerotic risk ( 14), has also been associated with FCH ( 15 ). In subjects with the syndrome ofinsulin resistance, also known as "syndrome X" ( 16,17), "familial dyslipidemic hypertension" ( 15,18), or the "deadly quartet" ( 19), clustering of risk factors may be found. This atherosclerotic state has also been called the "atherogenic lipoprotein phenotype" (20) and a candidate gene cluster comprising the insulin receptor and LDL receptor genes has been found on the short arm of chromosome 19 (21).…”
Section: Introductionmentioning
confidence: 99%
“…4,19,20 Castelli and Anderson 19 found that BP and serum cholesterol were strongly correlated among hypertensive patients, which led to early recommendations to treat elevated cholesterol in patients with hypertension. 5,19 Gaziano et al 21 also noted a potential interaction between elevated cholesterol and hypertension in the development of MI that suggested a direct relationship rather than the effect of 2 independent predictors.…”
Section: Discussionmentioning
confidence: 99%
“…To date, multivariate approaches to the MMS have only been demonstrated in a number of twin [32][33][34][35] and family studies [36]. These studies have pointed towards strong genetic or shared environmental influences on the joint occurrence of MMS components [32,33]. Recently, Mitchell et al [36] suggested that a common gene or set of genes may influence components of the MMS such as insulin, BMI, triglycerides, and HDL-cholesterol.…”
mentioning
confidence: 99%